Challenges and Solutions in School Management in the Binduriang Sub-District: A Descriptive Qualitative Approach - Asha, H. Lukman; Hamengkubuwono, H.; Yanto, Murni; Apriani, Eka; Alhajj, Irfan Qowwiyul Aziz (Journal of Teaching and Learning, 2025)
This study examines the management of education in a crime-prone area, specifically through a case study in the Binduriang district of Rejang Lebang district of Bengkulu province, Indonesia. This area is known for its high crime rates, which are especially associated with drugs, gambling, theft, and robbery. The study used a descriptive qualitative approach, collecting data through semi-structured interviews and open-ended questionnaires from nine school principals and 10 teachers in the Binduriang subregion. The data analysis used thematic analysis, which included transcription, manual and NVivo coding, categorization, and subject identification to ensure strict pattern recognition and reliable findings. The results show that the main challenges in managing Binduriang education include limited human resources, insufficient financial resources, and a lack of community participation and educational awareness. The study also highlights a number of solutions implemented, such as improving teachers' skills through workshops, and collaborating with security forces and other stakeholders. In addition, the study proposes practical plans to improve the quality of education, including the formation of a strong management team. It also aims to contribute to the understanding and resolution of educational management problems in crime-prone areas, and can serve as a model for other regions facing similar challenges.